Modifiable cardiovascular risk factors in patients with Behçet's disease: a multicenter experience - Emad El-Shebiny; Amira El-Fakharany; Enas Zahran; Sabry Shoeib; Mohamed Salem; Mohammed Elnaggar; Nibal Morad (SpringerOpen, 2019)
Background Vascular involvement in Behçet's disease (BD) is one of the major causes of mortality and morbidity. Modifiable cardiovascular risk factors such as high blood pressure, dyslipidemia, hyperglycemia, overweight, and smoking have been demonstrated to have a significant impact on cardiovascular disease in the general population with or without other diseases. Objective The aim of this study was to evaluate whether modifiable cardiovascular disease risk factors differ among patients with BD in comparison with the general population. Patients and methods This was a multicenter case-control study carried out on 182 BD patients identified by analysis of the databases of the International Study Group Classification Criteria. The patients were compared with 80 controls matched for age, sex, and study period. Full clinical history taking and medical examination were carried out for all patients, and investigations including lipid profile and blood glucose were carried out and data on hypertension, height, weight, and smoking were collected and recorded. Results Levels of serum low-density lipoprotein (P<0. 005) and cholesterol (P<0.005) were significantly high in the Behçet patient group, but no statistical difference was detected as regards triglycerides, diabetes mellitus, or BMI. Smoking and hypertension increase the risk of cardiovascular manifestations in our patients. The mean±SD age of BD patients was 31.6±9.008, 76.9% were male individuals and 23.1% were female individuals. Conclusion Patients with BD had a high prevalence of cardiovascular comorbidities. Optimal control of blood pressure, lipids and blood sugar with reduction in body weight and stoppage of smoking may be an effective strategy to reduce vascular complications in these populations.